Infection with HIV and hepatitis C virus among injecting drug users in a prevention setting: retrospective cohort study. Issue 7156 (15th August 1998) - van Beek, Ingrid; Dwyer, Robyn; Dore, Gregory J; Luo, Kehui; Kaldor, John M
Abstract: Objectives: To estimate the incidence of HIV and hepatitis C virus and risk factors for seroconversion among a cohort of injecting drug users. Design: Retrospective cohort study. Setting: Primary healthcare facility in central Sydney. Subjects: Injecting drug users tested for HIV-1 antibody (n=1179) and antibodies to hepatitis C virus (n=1078) from February 1992 to October 1995. Main outcome measures: Incidence of HIV-1 and hepatitis C virus among seronegative subjects who injected drugs and underwent repeat testing. Demographic and behavioural risk factors for hepatitis seroconversion. Results: Incidence of HIV-1 among 426 initially seronegative injecting drug users was 0.17/100 person years (two seroconversions) compared with an incidence of hepatitis C virus of 20.9/100 person years (31 seroconversions) among 152 injecting drug users initially negative for hepatitis C virus. Incidence of hepatitis C virus among injecting drug users aged less than 20 years was 75.6/100 person years. Independent risk factors for hepatitis C virus seroconversion were age less than 20 years and a history of imprisonment. Conclusions: In a setting where prevention measures have contributed to the maintenance of low prevalence and incidence of HIV-1, transmission of hepatitis C virus continues at extremely high levels, particularly among young injecting drug users.